IMPROVING THE CAPACITY OF HUMAN RESOURCES TO INCREASE PRODUCTIVITY OF BANANA CHIPS IN MSMEs - Agus Wiastono (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – The purpose of this study was to determine the model of human resource development carried out by banana chip SMEs to increase their sales turnover and the human resource development carried out by banana chip SMEs to increase sales turnover. Design/methodology/approach – This research is categorized as field research, namely, research carried out in the actual field or field, based on data obtained by researchers, both primary and secondary data. To obtain the right data and information, the data collection methods used include interviews, observation, and documentation by sampling the entire population as well as a sample of 32 MSME outlets. Findings – Based on the HR development carried out by all MSMEs of banana chips in increasing sales turnover and based on the Islamic Economic Perspective, it is considered not good. This is because of the 32 MSMEs as a whole, almost no one pays attention to the development of human resources, starting with the development of employee knowledge, employee skills, employee expertise, and employee insight. Only 2 MSMEs pay attention to the knowledge and skills of their employees because they carry out special training, especially in the field of marketing, namely e-commerce, improving services, and prioritizing branding. Research limitations/implications – This research is only used in some areas with a little sampling, but it is not representative of any research on the same idea. Maybe soon the researcher will use more sampling. Originality/value – One of the major impediments to the development of SMEs in East Java is the low quality of human resource development. This also happened to the MSMEs producing banana chips in Malang. Furthermore, several banana chip entrepreneurs experienced a drop in business, which had an impact on sales turnover. Keywords: MSME, HR development, Sales, Entrepreneurship Paper type: Case Study